2020
DOI: 10.1017/s0033291720000872
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive remediation for inpatients with psychosis: a systematic review and meta-analysis

Abstract: Cognitive difficulties are common in people with psychosis and associated with considerable disability. Cognitive remediation (CR) can reduce the burden of cognitive difficulties and improve functioning. While mental health care has predominantly shifted to the community, people with greater illness severity and complexity, and those with poor response to treatment and concomitant greater cognitive difficulties, continue to receive inpatient care. The aim of this study is to review and evaluate the acceptabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 73 publications
(123 reference statements)
1
31
0
1
Order By: Relevance
“…CCT is appealing as it can be adapted to individual needs, provides ongoing feedback and can be delivered inexpensively in both clinical and community settings. Support for CCT has been found for cognitive and functional outcomes across many clinical and non-clinical populations [13][14][15][16][17][18] , however, efficacy varies across populations, outcomes and design factors such as dose and supervision 13,14,17 .…”
Section: Introductionmentioning
confidence: 99%
“…CCT is appealing as it can be adapted to individual needs, provides ongoing feedback and can be delivered inexpensively in both clinical and community settings. Support for CCT has been found for cognitive and functional outcomes across many clinical and non-clinical populations [13][14][15][16][17][18] , however, efficacy varies across populations, outcomes and design factors such as dose and supervision 13,14,17 .…”
Section: Introductionmentioning
confidence: 99%
“…This evidence emphasizes that processing speed deficits are a potential intervention target to obtain better functional outcomes in patients with schizophrenia. Indeed, previous studies have demonstrated that cognitive intervention is effective for improving processing speed [ 22 ], even for inpatients with schizophrenia [ 34 ]. Taken together, these findings have important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous meta-analyses revealed significant improvement in different cognitive domains in schizophrenia after cognitive remediation [24][25][26] the meta-analysis by Revell et al [51] investigating CR efficacy in early schizophrenia showed a significant effect on verbal memory and learning, but only a non-significant small effect of CR on global cognition and other cognitive domains. Similarly, some randomized clinical trials also failed to report significant improvement [52][53][54], arguing the potential inefficacy of the cognitive remediation approach in schizophrenia patients in general [53] Both treatments in this study used a drill-practice approach.…”
Section: Cognitive Assessmentmentioning
confidence: 97%
“…The drill practice was reported as a beneficial intervention for increasing cognitive performance [22]; strategy learning was argued to lead to larger functional outcome performance [23]. Meta-analyses focusing on the effect of CR show more promising results than the treatment with antipsychotic medication [22,[24][25][26]. A large meta-analysis (n = 2401) conducted by Wykes et al [24], pointed to a moderate effect of CR on global cognitive functioning (ES = 0.45), and almost all cognitive domains showed significant improvement.…”
Section: Cognitive Remediationmentioning
confidence: 99%